KETIDAKPASTIAN HUKUM SYIBHUL IDDAH BAGI MANTAN SUAMI: STUDI EMPIRIS ATAS IMPLEMENTASI EDARAN DIRJEN BIMAS ISLAM DI KABUPATEN BATU BARA - Putri Rahma; Muhammad Iqbal Irham; M. Syahnan (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study examines the implementation of the Director General of Islamic Guidance Circular No. P-005/DJ.III/HK.00.7/10/2021 on recording the iddah period for women in KUA Medang Deras District, Batu Bara Regency, focusing on the legal uncertainty of syibhul iddah for former husbands. Using empirical legal research with qualitative methods, data were collected through in-depth interviews, participatory observation, and documentation analysis from KUA staff, former spouses, and community figures. Findings reveal consistent administrative recording of women's iddah but significant social pressure on former husbands to delay remarriage, creating normative confusion unsupported by fiqh or positive law. Through maqāṣid al-sharī'ah analysis, the practice is deemed redundant for nasab protection, disproportionate for honor safeguarding, and contrary to psychological well-being. Recommendations include revising the circular to clarify former husbands' status, enhancing KUA verification procedures, and maqasid-based socialization to achieve post-divorce legal certainty.